Analyzing the Impact of CNX Nifty Index Futures on the Volatility of S&P CNX Nifty Index - Karthikeyan, P.; Karthika, P. (Indian Journal of Research in Capital Markets, 2016)
Volatility plays an important role in the stock market. Investment decisions are made based on the volatility, apart from other significant factors like price, volume traded, liquidity, etc. Many new instruments have been introduced in the Indian stock market in the recent years to satisfy the needs of the investors and to enhance market efficiency. Index futures trading is one such instrument introduced in the year 2000 to reduce the systematic risk, improve investment strategy, and to achieve more efficient price discovery. Despite a continuous increase in the turnover of the index, futures trading raises the question, whether the equity market volatility increased or not due to the introduction of index futures. So, the present study examined the effect of futures trading on volatility of CNX Nifty. The study period was divided into pre-futures period and post-futures period. GARCH model was used to measure the volatility of CNX Nifty returns in pre-future period and post-future period separately. The results of the study indicated that introduction of index futures trading reduced CNX nifty volatility.